Dance and the Hollywood Latina : Race, Sex and Stardom. - Ovalle, Priscilla Peña (Rutgers University Press, 2010)
Dance and the Hollywood Latina asks why every Latina star in Hollywood history began as a dancer or danced onscreen. Introducing the concepts of "inbetween-ness" and "racial mobility" to further illuminate how racialized sexuality and the dancing female body operate in film, this book focuses on the careers of Dolores Del Rio, Rita Hayworth, Carmen Miranda, Rita Moreno, and Jennifer Lopez and helps readers better understand how the United States grapples with race, gender, and sexuality through dancing bodies on screen.
Keywords: Hispanic Americans in motion pictures.; Hispanic Americans in the motion picture industry.; Hispanic American motion picture actors and actresses.; Dance in motion pictures, television, etc. -- United States.; Race in motion pictures.; Sex in motion pictures.; Américains d'origine latino-américaine au cinéma.; Américains d'origine latino-américaine dans l'industrie cinématographique.; Race au cinéma.; Sexualité au cinéma.; ART -- Film & Video.; PERFORMING ARTS -- Film & Video -- Reference.; PERFORMING ARTS -- Film & Video -- History & Criticism.; Dance in motion pictures, television, etc.; Hispanic American motion picture actors and actresses; Hispanic Americans in motion pictures; Hispanic Americans in the motion picture industry; Race in motion pictures; Sex in motion pictures; United States